Analisis Pengaruh Debt to Equity Ratio (DER), Return On Equity (ROE), Current Ratio (CR), Terhadap Harga Saham (Pada Industri Pertambangan Yang Terdaftar Di BEI Tahun 2021-2024): Pada Industri Pertambangan yang Tercatat di BEI Tahun 2021-2024 - Jessika Ezar Harfianto; Hadi Pramono; Rina Mudjiyanti; Selamet Eko Budi Santoso (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
For mining businesses listed on the Indonesia Stock Exchange (IDX), the study's objective is to assess the impact of financial measures, namely the Debt-to-Equity Ratio (DER), Return On Equity (ROE), and Current Ratio (CR), on stock prices from 2021 to 2024. Purposive sampling is employed in a quantitative method. The approach used is quantitative with purposive sampling technique. From the total population, 179 companies were selected as the initial sample; however, after filtering and removing outlier data, the analysis was conducted on 145 observations. The annual financial reports of mining businesses that were posted on the IDX served as the source of the data that was examined. According to the study's findings, stock prices are not significantly impacted by DER or ROE. On the other hand, CR exhibits a notable impact. This result suggests that, when it comes to the mining industry, investors are more interested in firm liquidity than in capital structure or profitability when making investment decisions. In addition to providing empirical support for the corporate finance literature, this study can be used as a useful guide for businesses in the industry to build their managerial and investment plans.